POLITICAL CAREER AND MAIN POLITICAL DIRECTIONS OF XI PRESIDENCY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article reveals the political career of President Xi Jinping of the People's Republic of China before coming to power.